The Influence of Perceived Ease of Use and Perceived Usefulness on The Intention to Use BSI Mobile (Among Grocery Traders in Tanah Abang Market with Attitude Toward Using as An Intervening Variable) - Priyanto Priyanto; Fedianty Augustinah; Liling Listyawati; Damayanti Sri Lestari (Green Publisher Indonesia, 2024)
This study uses the Technology Acceptance Model (TAM) approach to examine the factors that influence how wholesalers in Tanah Abang Market perceive their interest in using BSI Mobile. These factors include perceived usefulness, ease of use, and attitude towards use. This research was conducted by sending questionnaires to wholesalers in Pasar Tanah Abang, Jakarta. A simple random sampling method was used to determine the sample size in this study. The questionnaire was sent to 109 food vendors in Tanah Abang Market who qualified as samples and analyzed with SPSS (Statistical Package for Social Sciences). The results showed that: (1) perceived usefulness has a significant influence on interest in using BSI Mobile, with a significance level of 0.038; (2) perception has a significant influence on interest in using BSI Mobile, with a significance level of 0.000; (3) perceived ease of use has a significant influence on interest in using BSI Mobile, with a significance level of 0.000; and (4) attitude towards use has a significant influence on interest in using BSI Mobile.